Knowledge and attitude regarding coronavirus disease-2019: an online survey of nursing staff from a tertiary care centre - Ukey, Ujwala; Sharma, Sarita K.; Rathod, Pragati; Patil, Sonali; Narlawar, Uday; Ughade, Suresh; Simon, Sophie (International Journal Of Community Medicine And Public Health, 2022)
Background: Currently, there is no specific antiviral treatment and preventive vaccine against COVID-19. Stringent practice of preventive measures is recommended as the only way out for protecting oneself. However, uncertainties galore and the prevention cannot be guaranteed due to paucity of knowledge about the epidemiology of COVID-19. Nurses are in an ideal position to participate or play a key role in taking initiatives to enhance patient safety during COVID-19 pandemic. Their knowledge will help to break the transmission chain. Methods: In the present cross-sectional study an online questionnaire was used for data collection from nursing staff employed in a tertiary care centre/dedicated COVID hospital in central India. Universal sampling was done and the final sample size attained was 932. Data was cleaned, coded and analysis was done with statistical package for the social sciences (SPSS) version 20.0. Percentages, means and standard deviations (SD) were calculated and statistical tests in the form of t test and Wilcoxon rank-sum (Mann-Whitney) test were applied. Results: Social-media and television (TV) were the main sources of knowledge about COVID-19 for the study participants as reported by 76.82% and 74.25% respectively. Study participants were aware about the common symptom of COVID-19 like cough, 127 (13.63%), fever 30 (3.22%), and diarrhoea 80 (8.58%). Conclusions: Irrespective of their age and gender study participants had a fairly good knowledge about symptoms and prevention of COVID-19. Most of them were optimistic and had a positive attitude towards COVID-19 pandemic and resultant situation.